Basic Legal Theory in Indonesian Constitution: Reviewing Developmental, Progressive, and Pancasila Legal Theories - Andri Prasetio (UIN Sunan Gunung Djati Bandung, 2022)
Three legal origin theories of Indonesia have influenced the development of study and practice of Law in Indonesia, whether in its thought, creation, implementation, and enforcement. Those three theories are Mochtar Kusumaatmadja's Developmental Legal Theory, Satjipto Rahardjo's Progressive Legal Theory, and Romli Atmasasmita's Integrative Legal Theory. Developmental Legal Theory has been criticized by Progressive Legal Theory and Integrative Legal Theory which rebuilds both Developmental Legal Theory and Progressive Legal Theory. It proves that a theory is built based on previous theories. Viewing these theories (the Developmental Legal Theory, Progressive Legal Theory, and Integrative Legal Theory) from a convergence point generates the Legal Theory of Five Principles known as Pancasila. All these theories are based on living Law in society and primordial values of Indonesian, which are the values of Pancasila as peculiar of social life and volkgeist. Legal Theory of Pancasila is a legal theory based on the importance of Pancasila as an ontological, epistemological and axiological foundation.